Помогите срочно!!!!!!!даю 40 баллов упростите выражение: а)4(m-1) - (2m+1)^2 б) (1-3c)^2+3(2c+1) в)k(2-5k) - (2-3k)^2 г)(7x+4)^2 - 4x(5-2x) д)(p+6)(6-p)+(p+2)^2 е)(p+6)(6-p)+(p+2)^2 ж)(x+3)(x-3) -(x+5)^2 з)(1-2y)^2 - (2y-3)(2y+3)

Помогите срочно!!!!!!!даю 40 баллов упростите выражение: а)4(m-1) - (2m+1)^2 б) (1-3c)^2+3(2c+1) в)k(2-5k) - (2-3k)^2 г)(7x+4)^2 - 4x(5-2x) д)(p+6)(6-p)+(p+2)^2 е)(p+6)(6-p)+(p+2)^2 ж)(x+3)(x-3) -(x+5)^2 з)(1-2y)^2 - (2y-3)(2y+3)
Гость
Ответ(ы) на вопрос:
Гость
а)4(m-1) - (2m+1)^2= 4m-4-4m^2-4m-1=-5-4m^2 б) (1-3c)^2+3(2c+1)=1-6c+9c^2+6c+1=2+9c^2 в)k(2-5k) - (2-3k)^2=2k-5k^2-4+12k-9k^2=14k-14k^2-4 г)(7x+4)^2 - 4x(5-2x)=49x^2+56x+16-20x+8x^2=57x^2+36x+16 д)(p+6)(6-p)+(p+2)^2=6p-p^2+36-6p+p^2+4p+4=4p+40 е)(p+6)(6-p)+(p+2)^2=6p-p^2+36-6p+p^2+4p+4=4p+40 ж)(x+3)(x-3) -(x+5)^2=x^2-9-x^2-10x-25=-34-10x з)(1-2y)^2 - (2y-3)(2y+3)=1-4y+4y^2-4y^2-9=-8-4y
Не нашли ответ?
Ответить на вопрос
Похожие вопросы